An experimental investigation of violations of transitivity in choice under uncertainty - Michael H. Birnbaum; Ulrich Schmidt (Kiel Institute for the World Economy (IfW), 2008)
Several models of choice under uncertainty imply systematic violations of transitivity of preference. Our experiments explored whether people show patterns of intransitivity predicted by these models. To distinguish "true" violations from those produced by "error", a model was fit in which each choice can have a different error rate and each person can have a different pattern of true preferences that does not need to be transitive. Error rate for a choice is estimated from preference reversals between repeated presentations of the same choice. Our results showed that very few people repeated intransitive patterns. We can retain the hypothesis that transitivity best describes the data of the vast majority of participants.
Keywords: C91; D81; 330; Errors; Regret theory; Transitivity; Decision making; Entscheidung bei Risiko; Präferenztheorie; Experiment; Theorie